Pertanggungjawaban Perdata terhadap Sertifikat Hak Atas Tanah sebagai Hak Tanggungan yang Hilang - Wirawan, Vani (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2022)
This study aims to find out and examine how civil liability for land rights certificates as mortgages is lost. This research is descriptive with the type of normative legal research. The results of the research analysis are mediation without going through legal channels (with a settlement, namely the management of loss of land rights certificates by creditors, and issuance of replacement certificates) as well as compensation. However, if the debtor wants to sue the creditor, it can be through a civil lawsuit, namely the debtor must use litigation, namely a lawsuit against the law.